Vitamin D Deficiency Prevalence in Late Neonatal Hypocalcemia: A Multicenter Study - Gülcan Seymen-Karabulut (Galenos Yayincilik, 2021)
Objective:Late neonatal hypocalcemia (LNH) is a common metabolic problem associated with hypoparathyroidism, high phosphate intake and vitamin D deficiency, often presenting with seizures. In this cross-sectional study, we aimed to evaluate the role of vitamin D deficiency in LNH in Turkey and to describe the characteristics of affected newborns.Methods:Conducted with a cross-sectional design and with the participation of 61 neonatal centers from December 2015 to December 2016, the study included term neonates with LNH (n=96) and their mothers (n=93). Data were registered on the FAVOR Web Registry System. Serum samples of newborns and mothers were analyzed for calcium, phosphate, magnesium, albumin, alkaline phosphatase, intact parathyroid hormone (iPTH) and 25 hydroxyvitamin D [25(OH)D] levels.Results:The median (range) onset time of hypocalcemia was 5.0 (4.0-8.0) days of age, with a male preponderance (60.4%). The median (range) serum 25(OH)D levels of the neonates and their mothers were 6.3 (4.1-9.05) and 5.2 (4.7-8.8) ng/mL, respectively. The prevalence of vitamin D deficiency (<12 ng/mL) was high in both the neonates (86.5%) and mothers (93%). Serum 25(OH)D levels of the infants and mothers showed a strong correlation (p<0.001). While the majority (93.7%) of the neonates had normal/high phosphorus levels, iPTH levels were low or inappropriately normal in 54.2% of the patients.Conclusion:Vitamin D deficiency prevalence was found to be high in LNH. Efforts to provide vitamin D supplementation during pregnancy should be encouraged. Evaluation of vitamin D status should be included in the workup of LNH.